1997
DOI: 10.1002/(sici)1097-0185(199708)248:4<566::aid-ar8>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nerve endings in cat extraocular muscles

Abstract: Background The aim of the present study was to identify the varieties of sensory and motor nerve endings in cat extraocular muscles. Methods Sensory terminals were identify by injecting neuronal tracers (fast blue, biocytin, or peroxidase) into the trigeminal ganglion, which contains the sensory cells innervating the eye muscles. Motor terminals were identified by injections of horseradish peroxidase or DiI, a fluorescent carbocyanin dye, into either the oculomotor nerve or the IIIrd nuclei. Results Injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 45 publications
1
67
0
Order By: Relevance
“…While such a correlation does not represent proof of this connection, it may explain the divergent findings across studies; i.e., a small and variable number of spindles may lead to variable labeling of a small number of MesV cells. While palisade endings are the only type of fiber specialization consistently found in vertebrate extraocular muscles, a number of other types of putative proprioceptors have been observed (Billig et al, 1997; Blumer et al, 2006; see Büttner-Ennever et al, 2006 for review). In fact, the quantity, distribution and subtypes of extraocular muscle endings vary between species, and perhaps even between individuals (Maier, 2000; Büttner-Ennever et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…While such a correlation does not represent proof of this connection, it may explain the divergent findings across studies; i.e., a small and variable number of spindles may lead to variable labeling of a small number of MesV cells. While palisade endings are the only type of fiber specialization consistently found in vertebrate extraocular muscles, a number of other types of putative proprioceptors have been observed (Billig et al, 1997; Blumer et al, 2006; see Büttner-Ennever et al, 2006 for review). In fact, the quantity, distribution and subtypes of extraocular muscle endings vary between species, and perhaps even between individuals (Maier, 2000; Büttner-Ennever et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…6,32,44,45 Because classic proprioceptors such as muscle spindles and Golgi tendon organs are absent in cat EOMs, Porter and Spencer 32 concluded that the labeled neurons in the trigeminal ganglion innervate the palisade endings. In anterograde tracing experiments Billig et al 23 injected neuronal tracers into the trigeminal ganglion of cats and found three different kinds of labeled nerve endings in the EOMs, one type resembling palisade endings.…”
Section: Palisade Endings As Sensory Organsmentioning
confidence: 99%
“…Several groups 6,16,[21][22][23]26,[32][33][34] have suggested that palisade endings could be the source of afferent signals, but there are still conflicting reports on the functional nature of palisade endings, whether they are sensory 6,16,[21][22][23]26,[32][33][34] or motor 28,35 structures, or both. 30 Fine structural analyses on palisade endings in cats, rhesus monkeys, and sheep have indicated a sensory function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we used cats because this species has palisade endings in the myotendinous nerve similar to those of humans [28,29]. The dose of botulinum toxin used in experimental studies varies, though it is typically in the range of 2-10 IU [17,25,30,31].…”
Section: Discussionmentioning
confidence: 99%